2011
DOI: 10.1007/s00431-011-1401-1
|View full text |Cite
|
Sign up to set email alerts
|

Early diagnosis of cerebral X-linked adrenoleukodystrophy in boys with Addison’s disease improves survival and neurological outcomes

Abstract: Approximately one-third of boys with X-linked adrenoleukodystophy (X-ALD) develop an acute, progressive inflammatory process of the central nervous system, resulting in rapid neurologic deterioration and death. Hematopoietic cell transplantation (HCT) can halt the progression of neurologic disease if performed early in the course of the cerebral form of X-ALD. We describe a retrospective cohort study of 90 boys with X-ALD evaluated at our institution between 2000 and 2009, to determine if early diagnosis of X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
37
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 20 publications
0
37
0
1
Order By: Relevance
“…For example, in 1997, Korenke et al reported that adrenal symptoms preceded neurological symptoms in 92 % of children with CCALD (Korenke et al 1997). In 2011, LE Polgreen et al noted that adrenocortical insufficiency was the first symptom of X-linked adrenoleukodystrophy in 38 % of patients (Polgreen et al 2011). Our observation was consisted with the current clinical data.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…For example, in 1997, Korenke et al reported that adrenal symptoms preceded neurological symptoms in 92 % of children with CCALD (Korenke et al 1997). In 2011, LE Polgreen et al noted that adrenocortical insufficiency was the first symptom of X-linked adrenoleukodystrophy in 38 % of patients (Polgreen et al 2011). Our observation was consisted with the current clinical data.…”
Section: Discussionmentioning
confidence: 95%
“…c Patient 11, the white matter highintensity lesions on FLAIR T2-weighted images involved the trigon of lateral ventricles and the splenium of corpus callosum before transplantation. d Patient 11, compared to the pre-transplantation MRI, the white matter high-intensity signals on FLAIR T2-weighted images extended to parietal lobe, midbrain, pons and cerebral peduncle 1 year after transplantation with a Loes score B0^, would improve both neurological outcomes and survival (Polgreen et al 2011). Weston P. Miller et al recently suggested that for patients without cerebral disease at the time of X-linked adrenoleukodystrophy diagnosis, serial neurologic, neuropsychometric and radiopraphic (brain MRI) testing with expeditious HSCT at the earliest evidence of active cerebral disease were recommended .…”
Section: Discussionmentioning
confidence: 98%
“…Surveillance for affected males includes periodic reevaluation (at least annually) of adrenocortical function by measuring ACTH and cortisol levels. 4 In select circumstances, an ACTH stimulation test may be necessary, but it should be noted that most individuals (.70%) will develop adrenal insufficiency.…”
Section: Sectionmentioning
confidence: 99%
“…The diagnosis of cerebral ALD was based on the presence of increased plasma VLCFA levels and characteristic white matter changes on MRI. 5 A pre-transplant diagnosis of AI was made at either the referring institutions or at our institution as recently published. 5 A group of 20 ALD patients, who returned for a follow-up visit, had a low-dose Cosyntropin (synthetic adrenocorticotropic hormone (ACTH) 1 - 24) stimulation test 1 - 7 years post HCT (one patient did not proceed with the stimulation test because a random ACTH level was markedly elevated at 1749 pg/mL).…”
mentioning
confidence: 99%
“…Cortisol level was measured at baseline and + 15, + 30, and + 60 min after i.v. administration of 1 mcg of Cosyntropin, 5 with AI diagnosed if the peak stimulated cortisol level was less than 20 mg/dL. A low-dose ACTH stimulation test was chosen because it is more sensitive for the diagnosis of subclinical AI than a standard dose (250 mcg) test.…”
mentioning
confidence: 99%